Gender assessment of job stress in healthcare workers. Implications for practice - d'Ettorre, Gabriele; Vullo, Annamaria (La Medicina del Lavoro, 2019)
Background: Work-related stress (WRS) in the healthcare sector is a major issue for both workers and organizations. To date, no consensus exists regarding differences in gender susceptibility to WRS in healthcare workers (HCWs). Objectives: The purpose of this study was to analyze how male and female HCWs employed in emergency departments experienced WRS. Methods: A cross-sectional study was conducted regarding the perception of WRS in registered nurses employed in emergency departments. The Italian version of the Job Content Questionnaire and the Rapid Stress Assessment scale were administrated to 710 registered nurses. Results: The WRS assessment showed that significantly more females than males were in a situation of isostrain (18.5% vs 9.8% p